International Students and Ambiguous Pedagogies within the UK Art School. (October 2016) - Davey, Annie
Abstract: This article will consider the tensions and opportunities provoked by the presence of a growing number of international students at UK art schools in which ambiguity operates as an implicit value within fine art pedagogies. Challenging assumptions of lack or deficit this article will ask how responding to this changing student body might require thinking beyond the horizon of normative claims and attitudes of the art school toward a situation in which it is constituted through the divergent perspectives, and pays attention to the previous educational experiences, of its students. I suggest that this requires the art school to address with greater commitment its pedagogical dimension in order to live up to its 'promise' as a heterotopic space.